Analisis Mitigasi Risiko Bisnis Cabai Rawit (Capsicum Frutescens L.) Kelompok Tani Salonro Jaya Dengan Pendekatan House Of Risk (Hor): Risk Mitigation Analysis of Bird’s Eye Chili (Capsicum frutescens L.) Agribusiness in the Salonro Jaya Farmer Group Using the House of Risk (HOR) Approach - Andi Hermina Julyaningsih; Ibnu Mansyur Hamdani; Irmayani (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2026)
Bird’s eye chili is one of the food commodities that is consistently available and highly demanded, particularly by consumers in the Indonesian market. However, the unstable supply of chili causes significant price fluctuations in the market. The Salonro Jaya Farmer Group is one of the farmer groups cultivating bird’s eye chili as their main commodity in Bantaeng Regency. Price fluctuations of bird’s eye chili in the market result in uncertain income for the Salonro Jaya Farmer Group. During simultaneous harvest seasons across several regencies, the selling price of bird’s eye chili drops drastically to as low as IDR 5,000 per kilogram, while the normal price is approximately IDR 20,000 per kilogram. Farmers who sell their produce during this period experience substantial losses, as production costs exceed the revenue obtained from chili sales. Several strategies can be implemented to minimize losses and maximize farmers’ income. However, limitations in resources such as labor, financial capacity, and technology require farmers to prioritize the most urgent problems and mitigation strategies. The House of Risk (HOR) method is used to analyze potential risk events and risk agents and to determine priority mitigation strategies. The analysis of 25 risk events and 24 risk agents identified 14 major risk agents and corresponding mitigation strategies. The final results of the HOR analysis indicate three priority strategies that should be immediately implemented by the Salonro Jaya Farmer Group: (1) conducting training on value-added processing of bird’s eye chili, (2) establishing a Zero Energy Cool Chamber (ZECC) to extend the shelf life of bird’s eye chili, and (3) diversifying marketing channels through e-commerce and HORECA (hotel, restaurant, and café) markets.